Ethical Deepfake Governance: EU AI Act Benchmarks and Indonesia Multi-Stakeholder Responses - Juan Pratama (Jurist-Diction, 2026)
AI-based deepfakes pose a threat to the digital community. Their massive spread has led to various problems, including fraud, threats to social cohesion, reputational damage, and the erosion of social values. Based on this, researchers conducted a study on AI-based deepfakes in Indonesia and formulated comprehensive provisions and strategies to address them. The researchers used a normative legal research method, drawing on regulatory, conceptual, case, and comparative law approaches. Furthermore, this study focused on the urgency of regulating AI-based deepfakes within Indonesia's positive legal system, the formulation of regulations based on comparisons with the EU AI Act, and management strategies that emphasize multiparty elaboration. In this case, this research produced a formulation of AI-based deepfake provisions in Indonesian positive law and a strategy for handling the misuse of this technology, namely the SMART-G Framework. It is hoped that this strategy can unite regulation, technology, and public participation to create a fair digital space in Indonesia.